IMPROVING THE NUMERATION AND LITERATURE CAPABILITIES OF CLASS III STUDENTS IN SIMARHOMPA 177041 ELEMENTARY SCHOOLS THROUGH THE CAMPUS TEACHING PROGRAM - Silitonga, Njuah Moenda Sari; Herman, Herman; Sherly, Sherly; Julyanthry, Julyanthry; Tannuary, Arwin; Sinurat, Bloner; Simangunsong, Rosma; Sitanggang, Anita (LPPM Univ. Ibn Khaldun Bogor, 2022)
With the coronavirus, the activities of the community have been disrupted. So that it has an impact on the Indonesian people, especially in the world of education. Since the COVID-19 pandemic, learning in Indonesia has been held online. The purpose of carrying out teaching activities at simarhompa 177041 elementary schools is to improve the literacy and numeracy skills of third-grade elementary school students by utilizing the independent campus program with campus teaching by students. This campus teaching activity is carried out from August 9, 2021, to December 17, 2021. The schedule of activities includes assignments, the deployment of campus teaching participants, the teaching process, mentoring with field lecturers student withdrawals, and closings. After the implementation of campus teaching was completed, this program proved to be very beneficial for students and schools. Both as they study and as they program with other students, students gain a wealth of practical experience in the field. Placement schools, on the other hand, recognize that the presence of students on site is very helpful for them in terms of teaching programs, assisting with technology adaptation, and assisting school administration and teachers.